SEKTOR INFORMAL DAN PEREMPUAN PKL (Studi di Pasar Bambu Kuning Bandar Lampung) - Benjamin Benjamin (SOSIOLOGI: Jurnal Ilmiah Kajian Ilmu Sosial dan Budaya, 2014)
This research aims to identify and explain about the informal sector and women street vendors, Yellow Bamboo Market Studies at Bandar Lampung. This research method took 6 informants women street vendors who trade with the type of merchandise that is different. The method used is descriptive method and purposive sampling. Data collection techniques with in-depth interviews and documentation. It was concluded that women with street vendors selling a variety of means, such as kiosks, tents and spread out his wares on the pavement or bare floor and above or in crates stacked serves as a table. Although at the time of selling them hung in a particular place, the women of the street vendors where the mobile is easy to move merchandise to another location. They can customize the location and time of selling the crowds condition somewhere, but often have to deal with market forces or official order.